1999
DOI: 10.1071/ah990141
|View full text |Cite
|
Sign up to set email alerts
|

Managing unstable angina and coronary care beds effectively

Abstract: This article is an evaluation of a new chest pain admission policy at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Our results were similar to previous studies of the CPP (Table 4). 13,17 In this study, patients with chest pain suspected to be of ischaemic origin who had a normal or unchanged initial ECG, no recurrent chest pain requiring IV GTN nor initial CK rise would have had no life‐threatening arrhythmias, no deaths nor cardiac arrest in the first 72 h of admission and few adverse events overall. The CPP triaged 60% fewer patients to an MNB than strict adherence to NHMRC recommendations.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Our results were similar to previous studies of the CPP (Table 4). 13,17 In this study, patients with chest pain suspected to be of ischaemic origin who had a normal or unchanged initial ECG, no recurrent chest pain requiring IV GTN nor initial CK rise would have had no life‐threatening arrhythmias, no deaths nor cardiac arrest in the first 72 h of admission and few adverse events overall. The CPP triaged 60% fewer patients to an MNB than strict adherence to NHMRC recommendations.…”
Section: Discussionmentioning
confidence: 79%
“…This study thus externally validated the application of the CPP for ED disposition of chest pain patients. It adds to the weight of evidence in the literature questioning the role of CCM for all patients with chest pain 1–4,12 , 13,17 , 22,23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a few studies that have examined whether an ED ACS diagnosis is subsequently confirmed after admission to a hospital ward. Kelly et al 10 followed all patients who were diagnosed in ED with UA and admitted to a coronary care unit over a 2 month period. They found that the admission diagnosis of ischaemic cardiac pain (MI, UA or angina) was confirmed in 80% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…The development of the Western Hospital Chest Pain Protocol (WHCPP) has taken place over several years. Its development and a pilot validation have been reported previously 5−7 . It identifies patients in the emergency department (ED) who require hospital admission for evaluation and treatment of suspected ACS and who, based on clinical, ECG and biochemical data, are at low risk of cardiac events during hospitalization.…”
Section: Introductionmentioning
confidence: 99%